2014
DOI: 10.1098/rsif.2014.0623
|View full text |Cite
|
Sign up to set email alerts
|

The digital traces of bubbles: feedback cycles between socio-economic signals in the Bitcoin economy

Abstract: What is the role of social interactions in the creation of price bubbles? Answering this question requires obtaining collective behavioural traces generated by the activity of a large number of actors. Digital currencies offer a unique possibility to measure socio-economic signals from such digital traces. Here, we focus on Bitcoin, the most popular cryptocurrency. Bitcoin has experienced periods of rapid increase in exchange rates (price) followed by sharp decline; we hypothesize that these fluctuations are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
237
3
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(276 citation statements)
references
References 29 publications
11
237
3
6
Order By: Relevance
“…Bouoiyour, Selmi, Tiwari, & Olayeni (2016) stated that bitcoin's price is determined by the long-term fundamentals, including the supply and demand fundamentals. The fluctuation in bitcoin's price is also influenced by the new adopters of bitcoin itself, or as can be said, the new users and it's spread by word of mouth (Garcia, Tessone, Mavrodiev, & Perony, 2014). The research by Polasik, Piotrowska, Wisniewski, Kotkowski, and Lightfoot (2015) found that the rising number of bitcoin users, whether they treat bitcoin as an investment or as a payment media, also drives the price of bitcoin.…”
Section: Related Workmentioning
confidence: 99%
“…Bouoiyour, Selmi, Tiwari, & Olayeni (2016) stated that bitcoin's price is determined by the long-term fundamentals, including the supply and demand fundamentals. The fluctuation in bitcoin's price is also influenced by the new adopters of bitcoin itself, or as can be said, the new users and it's spread by word of mouth (Garcia, Tessone, Mavrodiev, & Perony, 2014). The research by Polasik, Piotrowska, Wisniewski, Kotkowski, and Lightfoot (2015) found that the rising number of bitcoin users, whether they treat bitcoin as an investment or as a payment media, also drives the price of bitcoin.…”
Section: Related Workmentioning
confidence: 99%
“…This research follows the methodology employed by Lee (2009) which looked at factors influencing the adoption of internet banking. Bitcoin adoption, like the adoption of internet banking, involves the acceptance of an innovative technology, along with social systems and personal characteristics (Bashir et al, 2016;Garcia et al, 2014;Grinberg, 2011;Lee, 2009). As with Lee (2009), this research employs two research streams, the information technology adoption theory and perceived risk theory, to develop the research model and hypotheses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To achieve such aim, the following research questions are investigated: (1) This paper is based on a study by Lee (2009) which looks at factors influencing the adoption of internet banking. It is believed that, as with internet banking adoption, Bitcoin adoption involves the acceptance of an innovative technology along with the effects of social phenomena and personal characteristics (Bashir, Strickland, & Bohr, 2016;Garcia, Tessone, Mavrodiev, & Perony, 2014;Grinberg, 2011;Lee, 2009). This descriptive research used an online questionnaire for data collection from 237 South African members of virtual communities (VCs) and virtual investment communities (VICs).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also show that Bitcoin price formation is subject to unique factors that substantially differ from that affecting conventional assets. These factors include internet search (see, among others, Kristoufek, 2013), word-of-mouth information on social media, and information on google trends (Garcia et al, 2014). Eisl et al (2015) concentrate on the benefits of adding Bitcoin to an equity portfolio.…”
Section: Introductionmentioning
confidence: 99%